Preparation and Thermal Stress Analysis of Al2O3 Insulation Coatings on SS-304 Tape - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2009)
Al2O3 insulation coatings are grown on long-length stainless steel (SS) tapes using reel-to-reel sol-gel method for applications of HTS/LTS coils and magnets. Various ceramic solutions are prepared from Al based precursors, solvent and chelating agent, the coating are fabricated on SS substrates. Al2O3 solution was successfully obtained using Al-sec-butoxide precursor, and isopropanol and acetylacetone as solvent and chelating agents, respectively. In order to improve adhesion of Al2O3 on the SS-304 tapes, triethanolamine was used in the solution. The residual stresses are investigated at different temperature ranges, between (630, 600, 580, and 550 degrees C) and room temperature for different thicknesses (12, 10 and 7 mu m). The maximum stress values are obtained as 0.756 GPa as tension on substrate (SS) for the 12 mu m coating and 1.0 GPa as compression for the 7 mu m Al2O3 coating at 630 degrees C. The surface morphology and microstructure of samples are characterized by a scanning electron microscope (SEM). SEM observation revealed that Al2O3 coatings have crack and mosaic structure.
Keywords: Al2O3; electrical insulation and superconducting magnet; sol-gel; thermal stress